2022
DOI: 10.3389/fgene.2021.810793
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chromosomal Instability in Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a malignant tumor of the central nervous system (CNS). The poor prognosis of GBM due to resistance to therapy has been associated with high chromosomal instability (CIN). Replication stress is a major cause of CIN that manifests as chromosome rearrangements, fragility, and breaks, including those cytologically expressed within specific chromosome regions named common fragile sites (CFSs). In this work, we characterized the expression of human CFSs in the glioblastoma U-251 MG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…In our previous study, we applied Cen-CO-FISH to reveal a mechanism dependent on CENP-A and its associated proteins to prevent centromere recombination in human cells, which also increases in replicative senescence and in cancer cells (Giunta and Funabiki, 2017). CENP-A contributes to centromere DNA stability (Black and Giunta, 2018) and to preventing mutagenic R-loop-induced DNA damage and chromosome rearrangements (Balzano et al, 2021;Giunta, Hervé, et al, 2021). We also found that CENP-A depletion causes an apparent increase in the chromatin volume occupied by α-satellites along with altered sphericity of centromeres (Giunta and Funabiki, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we applied Cen-CO-FISH to reveal a mechanism dependent on CENP-A and its associated proteins to prevent centromere recombination in human cells, which also increases in replicative senescence and in cancer cells (Giunta and Funabiki, 2017). CENP-A contributes to centromere DNA stability (Black and Giunta, 2018) and to preventing mutagenic R-loop-induced DNA damage and chromosome rearrangements (Balzano et al, 2021;Giunta, Hervé, et al, 2021). We also found that CENP-A depletion causes an apparent increase in the chromatin volume occupied by α-satellites along with altered sphericity of centromeres (Giunta and Funabiki, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of breaks and gaps on mitotic chromosomes remains enigmatic, as they can be presented by single-stranded DNA, double-strand DNA breaks or decondensed chromatin. Therefore, cytogenetic analysis remains relevant for studying cFS (Miron et al, 2015;Balzano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%